A SynB1-conjugated antibody cocktail crosses the blood–brain barrier to produce a therapeutic effect on rabies - Zeheng Ren; Caiqian Wang; Haoran Wang; Qiong Wu; Qingxiu Hou; Xue Qi; Wenna He; Xiaoyu Zhang; Jiawu Wan; Zhen F. Fu; Ming Zhou; Ling Zhao (Proceedings of the National Academy of Sciences, 2025)
Rabies, caused by the neurotropic lyssavirus rabies virus (RABV), is nearly 100% fatal after symptom onset. A fundamental challenge for rabies therapy is that the blood–brain barrier (BBB) prevents peripherally administered neutralizing antibodies from entering the central nervous system (CNS) to clear the infection. In this study, we initially generated four human–mouse chimeric antibodies with preserved neutralizing potency against RABV to increase its translational potential. To achieve brain antibody delivery, we conjugated a lead chimeric antibody (7A3-H) to different cell-penetrating peptides with potential BBB-penetrating capacity (RVG, TGN, THR, and SynB1). In vivo fluorescence imaging revealed that SynB1 conjugation significantly outperformed conjugation with the other peptides in terms of BBB penetration for brain antibody delivery. Furthermore, a triple-antibody cocktail (targeting epitopes II/III/IV of RABV-G) conjugated to SynB1 resulted in 80% survival in mice infected with lethal challenge virus standard (CVS) or dog-originated rabies virus (DRV) strains when it was administered at 5 dpi (when CNS invasion and symptoms were evident). In contrast, the unconjugated cocktail provided only 20% (CVS) or 0% (DRV) survival. Together, these data demonstrated that SynB1-mediated BBB penetration dramatically improved the therapeutic efficacy of anti-RABV antibodies, enabling post-symptom rescue of rabies. This antibody–peptide conjugation strategy provides a proof of concept for advancing rabies therapy, specifically by leveraging peptide-mediated enhancement of BBB penetration.